Is MonoMart with an Islamic context: Monopoly-smart media effective in elementary school game-based mathematics learning? - Pandia, Weny Savitry S.; Suharsiwi, Suharsiwi; Darmayanti, Rani; Araújo, Francisco Cleuton de (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2022)
Elementary mathematics education must include character guidance (honesty, hard effort, independence, social care, curiosity, faith, and responsibility) and mathematical understanding. To understand the wisdom gained from studying mathematics (life's mathematics). Advanced thinking is needed so students can build their mathematical image definitions. Thus, character education is necessary to apply mathematical concepts in the real world and address the issue of low student interest and math learning outcomes due to a need for more innovative and exciting learning media. Monopoly-smart Islamic monopoly learning media for elementary school game-based mathematics learning is the goal of this project. This research develops elemental school teaching media. We employed the Four-D development model: defining, designing, developing, and disseminating. This research is only design-related. This media was hand-designed, scanned, and Photoshopped. Islamic Math Monopoly is a mathematical monopoly on FPB and KPK conceptual material with Islamic nuances that teach character and math. After creating the first product, material, media, and math professors will validate it. Data analysis is described qualitatively. This research's material, language, and presentation results are "Very Appropriate." Thus, this medium is "Very Appropriate" and requires validator input, such as making the material more synchronous, adding challenge questions, and including KD/KI in writing. This research found that Islamic monopoly-smart media (MonoMart) games suit elementary school mathematics instruction